ความสัมพันธ์ระหว่างพลวัตประชากรปูม้า Portunus pelagicus (Linnaeus, 1758) กับปัจจัยทางกายภาพของแหล่งหญ้าทะเล อ่าวคุ้งกระเบน จังหวัดจันทบุรี - กุศล เรืองประเทืองสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Relationships between population dynamics of blue swimming crab, Portunus pelagicus (Linnaeus, 1758), and physical factors of seagrass bed, Khung Krabaen Bay, Chanthaburi Province was determined by the study of population dynamics of blue swimming crab in planktonic stage, post A settlement and adult in two different seagrass beds, Enhalus acoroides and Halodule pinifolia from April 2008 to March 2009. Different densities of planktonic stage, post A settlement and adult were recorded during daytime and nighttime. High densities of planktonic stage were found in dry season. These planktonic stages were found highest in E. acoroides seagrass beds. In respective ranking were the densities in H. pinifolia seagrass beds and bare ground. Results From the distribution and density of crab population in two peaks of spawning season during December 2008 A January 2009 and April 2009 A May 2009, showed the different densities of crab population in planktonic stage during day and night sampling and the two spawning periods. The estimation on the success of planktonic development to settlement was higher in the E. acoroides seagrass beds than H. pinifolia seagrass beds and bare ground. Juvenile blue swimming crab preferred the H. pinifolia beds while the adult crab preferred the bare ground. Carapace width of crabs in seagrass beds were smaller than crabs in bare ground. The sex ratio of male to female was 1 : 0.5. The relationships between carapace width and weight were W = 0.0963CW2.8264 and W = 0.1005CW2.7859 in male and female crabs, respectively. The data on crab population dynamics have been calculated by the FiSAT program based on carapace width and frequency distribution. The growth parameter of male crab were L∞ = 12.23 cm.; K = 0.56 per year while the growth parameter of the female crab were L∞ = 11.23 cm.; K = 1.10 per year while total mortality of male and female crabs were indicated by 1.43 and 0.83 per year, respectively The probability of capture (L50%) was 1.46 cm. The recruitment period occurred all year but with two peaks. The first peak was during June to August 2008 and the second peak was during December 2008 to February 2009. The physical factors of seagrass bed that influenced the distribution and density of planktonic stage are transparency, temperature and salinity. This study revealed the importance of seagrass beds in Khung Krabaen Bay, Chanthaburi Province in the recruitment of blue swimming crab populations as nursery ground for planktonic and post A settlement stages.